Perlindungan Hukum Bagi Kreditor dalam Kepailitan di Sektor Hulu Minyak dan Gas Bumi - Atika Ismail; Susiana Kifli (Universitas Batanghari Jambi, 2022)
One of the challenges or problems that develop during upstream oil and gas industry operations is bankruptcy. The oil and gas upstream industry faces a variety of challenges. These problems include managing Indonesia's oil and gas deposits, which are now concentrated mostly in the western half of the country, and the nation's small domestic oil and gas reserves in compared to other countries. Despite the fact that Indonesia's reserves cannot be described as substantial, they are nonetheless significant given the country's enormous population. A normative juridical methodology was employed to write this journal. Temuan penelitian tersebut dirinci dalam artikel jurnal ini mengenai status kasus kepailitan yang masih beredar di Indonesia, negara yang ekonominya sedang memasuki tahap krisis akibat penyebaran global pandemi Covid-19. In order for the data in bankruptcy cases to once more indicate a rise in the number of Commercial Court registrations.